Recurrent wheezing in a toddler - Mohammad Nasir, Zuraini; Mohd Salehuddin, Nur Syazwani; Abu Bakar, Saraiza (The Royal Australian College of General Practitioners, 2022)
A boy aged one year and seven months was brought by his mother to the general practice clinic with a three-month history of recurrent wheezing, especially when active. There were no symptoms of cough, fever, difficulty breathing or choking. There was no personal or family history of asthma, allergy or eczema. On further questioning, the boy’s mother was able to recall the first episode of wheezing at a birthday party. On examination, the child was active and not tachypneic. His vital signs were normal, and there was no stridor or audible wheezing. Lung auscultation revealed intermittent wheeze with equal breath sounds. Other examination findings were not significant